A Handbook and Reader of Ottoman Arabic. - Wagner, Esther-Miriam. (Semitic Languages and Cultures Series, 2021)
This volume is the first linguistic work to focus exclusively on varieties of Christian, Jewish and Muslim Arabic in the Ottoman Empire of the 15th to the 20th centuries, and present Ottoman Arabic material in a didactic and easily accessible way.